ANALISIS TEGANGAN KELUARAN DC-DC BOSST CONVERTER BERBASIS MIKROKONTROLER - Innsanur Resi Darmawan (Pusat Riset dan Inovasi Nasional, 2022)
In this study, an electric motorcycle has been successfully designed using a 48 V 25 Ah Lithium Polymer Battery. With the advantages possessed by this battery, it is hoped that it can help get a high level of efficiency during testing. This battery will later bear the burden of a BLDC motor with a power of 3 KW. In this test, 2 tests were carried out, namely with and without load. The results obtained are the efficiency value at no-load is 12.35% at the maximum speed of 40 Km/hour and 17.2% at the same speed under load conditions. With these results, it proves that the faster the motorbike goes, the higher the efficiency value will be due to the smaller torque so that it saves battery power.